Refractive errors in Thiqar secondary schooling graduate ?students: prevalence and determinants at 2016? - Assist prof.Dr. Ali Abid Saadoon (University of Thi-Qar Journal, 2022)
Background: Refractive error is consider as one of the main health problems of concern, that has real burden on community institutions and individuals Aim: The aim of this study was to assess the prevalence and subtypes of refractive errors in students want to be enrolled in the universities and institutions after completing of their secondary graduation, Methodology: A cross sectional analytical comparative study including a total of 4322 students attending the pre-enrollment fitness clinic in public health care center ,extended all over the last four months of the 2016; where routine medical examination before university enrollment underwent visual screening including uncorrected visual acuity, color vision, in addition to a slit-lamp examination. Students with a visual acuity of 6/9 or less in either eye undergo objective refraction and subjective verification to determine the best-corrected visual acuity. Results: A total of 4322 students were enrolled in this study,2030 males and 2292 females ; refractive error was found in. (35.8%) students, Myopia was the main type of refractive error Astigmatism then Hypermetropia (24.2%, 11.5%, 1.1%) respectively. Age , sex, address, average of suxcess and number of hours of using electronic devices was the main significant independent variables for the error of refraction occurance. Conclusion: Refractive error is a one of the common causes of visual impairment among the group of adolescents want to be enrolled for university education in different universities. The study enabled to understand trends of refractive error in Thiqarian students and demonstrated the importance of vision screening in providing timely eye care and identifying visually disabled secondary school students. Myopia is particularly more prevalent than that reported in other regions so early detection and correction is essential to avoid ametropic amblyopia.